On vertical electric fields at lunar magnetic anomalies. Issue 7 (2nd April 2014) - Jarvinen, R.; Alho, M.; Kallio, E.; Wurz, P.; Barabash, S.; Futaana, Y.
Abstract : We study the interaction between a magnetic dipole mimicking the Gerasimovich magnetic anomaly on the lunar surface and the solar wind in a self‐consistent 3‐D quasi‐neutral hybrid simulation where ions are modeled as particles and electrons as a charge‐neutralizing fluid. Especially, we consider the origin of the recently observed electric potentials at lunar magnetic anomalies. An antimoonward Hall electric field forms in our simulation resulting in a potential difference of <300V on the lunar surface, in which the value is similar to observations. Since the hybrid model assumes charge neutrality, our results suggest that the electric potentials at lunar magnetic anomalies can be formed by decoupling of ion and electron motion even without charge separation. Key Points: Quasi‐neutral hybrid simulation of lunar magnetic anomaly‐solar wind interaction Formation of antimoonward Hall electric field at lunar magnetic anomaly Hall electric field results in potential wall even without charge separation